A STUDY OF PULSATILE INCLINED FLOW UNDER PERIODIC BODY ACCELERATION - Sanamani, Jayashri (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A mathematical model has been formulated to study the pulsatile inclined two-layer blood flow under periodic body acceleration with magnetic field. The effect of periodic body acceleration and magnetic field on the blood flowing through a uniform inclined cylindrical tube has been analyzed.